ENGARUH KAPASITAS SUMBERDAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN VARIABEL INTERVENING SISTEM PENGENDALIAN INTERN PEMERINTAH Studi pada Satuan Kerja Perangkat Daerah Kota Cirebon - Deasy Hary Rahman Puspita; Dewi Amalia (Universitas Ahmad Dahlan, 2014)
he quality of local government financial reporting is influenced by several factors: human resources capacity, information technology utilization, and system of government internal control. Independent variable in this research are human resources capacity, information technology utilization, and system of government internal control as intervening variable, and quality of local government financial reporting as dependent variable. Respondents on this research are SKPD’s accounting departement in Cirebon. This research use purposive sampling with 84 respondents. The result found that human resources capacity have influence toward quality of local government financial reporting, while information technology utilization, and system of government internal control have not influence toward quality of local government financial reporting. The human resources capacity and information technology utilization have influence toward system of government internal control. The main requirement testing intervening variable is a variable system of government internal control have influence toward quality of local government financial reporting. The results showed tha system of government internal control have no influence toward quality of local government financial reporting.